ANALISIS BUKU AJAR (LEHRWERKANALYSE) BAHASA JERMAN STUDIO D DAN NETZWERK DALAM PENGAJARAN BAHASA JERMAN DI STBA YAPARI-ABA BANDUNG - Tintin Agustina; Dasim Karsam (Jurnal SORA, 2018)
A textbook plays a very crucial role in foreign language teaching. On the one hand, it deals with linguistic and cultural phenomena; Moreover, it controls the whole learning process for a certain period of time. This research focuses on the main learning materials and media used by lecturers and students of German Department at STBA YAPARI. The purpose of the study is to find a suitable textbook for them. In order to reach the goal of the investigation, this study uses the theoretical foundations of Rösler & Würffel (2014: 17-32) on the analysis of learning materials and media in a form of the textbook analysis method, namely the analysis of "Studio d" and "Netzwerk" A1-B1. The results of the study show that the new textbook has some advantages over the old one if the two textbooks consider (1) the components and their functions, (2) the internal structure, and (3) the language level Common European Framework of Reference for Languages (CEFRL) of textbooks. The importance of this research is that the plan for the renewal of learning materials and media should be implemented in the German Department in the 2018/2019 academic year. Another investigation can be done in the form of an evaluation of the implementation of learning materials and media in the classroom in the 2018/2019 academic year.